Study on Home-Based Direct Care Workers' Coping Responses to Workplace Sexual Harassment and Their Satisfaction With Long-Term Care Preventive Strategies (International Journal of Studies in Nursing, 2023)
Background Previous research on workplace sexual harassment issues in long-term care rarely focused on home-based direct care workers. Additionally, few victims would formally report the harassment incidents, resulting in limited understanding yet huge impacts on improving long-term care quality. Purpose Built upon Donabedian’s structure-process-outcome framework, this study aimed to explore home-based direct care workers’ coping responses when encountering workplace sexual harassment (WSH) and examine factors influencing their satisfaction with organizational preventive strategies. Methods This cross-sectional study surveyed 217 home-based caregivers via convenience sampling. Research instruments included socio-demographics, personal experiences (perceived job hazard and harm severity of WSH), and satisfaction scale ratings. Variance analysis, Pearson’s correlation, and hierarchical regression analysis were performed for statistical analysis. Results Caregivers working at private LTC agencies expressed lower satisfaction with employers’ anti-harassment measures than public agencies. Part-time workers also reported lower satisfaction. While 22% of participants took no actions when harassed, 30.8% directly told the harassers to stop. Manpower load status (r=-.16; p